SERVICE QUALITY AND BPJS PATIENT SATISFACTION AT THE MATERNAL AND CHILD HEALTH CLINIC (KIA) OF LEDOKOMBO HEALTH CENTER, JEMBER REGENCY - Dessy Yulianti; Harmawan Teguh Saputra; Hanif Hadinata Utama (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the relationship between BPJS patient satisfaction and the quality of maternal and child health (KIA) services at the Ledokombo Community Health Center. Patient satisfaction is a crucial indicator in assessing the success of healthcare services, particularly within the National Health Insurance (JKN) scheme implemented through BPJS. The KIA service, as a maternal health service at the community health center, possesses both clinical and interpersonal characteristics that influence patient perceptions of quality and satisfaction.Methods: This study used a quantitative analytical design with a correlational approach, involving 100 BPJS patients at the KIA Clinic of Ledokombo Community Health Center. Data were collected using a 5-point Likert-scale SERVQUAL questionnaire and analyzed using the Pearson Product-Moment correlation test in SPSS 2025.Results: The results show that service quality at the MCH clinic is classified as good, with Assurance and Responsiveness as the most prominent dimensions. Patients feel safe, trust healthcare providers, and receive fast and responsive services. A total of 76% of respondents reported being satisfied, although some were moderately satisfied or dissatisfied, particularly regarding communication and personal attention. Pearson analysis indicates a strong and significant positive relationship between service quality and patient satisfaction (r = 0.684; p = 0.000), thus the research hypothesis is accepted.Conclusion and suggestion: There is a significant relationship between service quality and BPJS patient satisfaction at the MCH clinic. Therefore, increased satisfaction can be achieved by strengthening clinical competence, service speed, and interpersonal communication. It is recommended that community health centers strengthen clinical communication training and optimize maternal service flows. Keywords: BPJS, KIA, Primary Health Care, Satisfaction, Service Quality